My brother's keeper : a mystery - Malane, Donna (Minotaur Books / A Thomas Dunne Book, 2017)
"From New Zealand author Donna Malane, My Brother's Keeper is a dark and twisting mystery that leave no stone -- or page -- unturned. Diane Rowe is a missing persons expert. Ex-con Karen needs Diane's help to track down her fourteen-year-old daughter, Sunny, whom she's lost contact with while she's been in prison. To Diane, this appears at first glance to be a simple case of a mother wanting to reunite with a beloved daughter. Tracking the girl down is easy. However, convincing her to meet her mother is no easy task. And at the back of Diane's mind is a nagging thought -- that guilt and innocence aren't straightforward and nothing is quite what it seems. Does Karen really want to fix the wrongs of the past or is there something darker at play here that will take all of Diane's skills to uncover? --